2015
DOI: 10.1080/14786419.2015.1007975
|View full text |Cite
|
Sign up to set email alerts
|

A new 3,4-seco-cycloartane from the leaves ofHopea odorataRoxb.

Abstract: A new 3,4-seco-cycloartane, identified as (24R,25S)-dihydroxy-26-O-nonadecylcarbonyloxy-3,4-secocycloarta-4(28)-en-3-oic acid (1), has been isolated from the leaves of Hopea odorata Roxb. (Dipterocarpaceae), together with the rare 3,4-seco-cycloart-4(28),24-diene-3,26-dioic acid (2 or abiesatrine J) and six other known compounds (3-8). Their structures were elucidated on the basis of both chemical and spectroscopic methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Of them, metabolites 1 – 6 belong to schitriterpenoids while 7 – 9 are schinortriterpenoids. Specifically, abiesatrine J ( 3 ) was a rare C-24/C-25 double bond isomer of nigranoic acid ( 1 ) and was only found in two plants, Abies georgei Orr ( Yang et al, 2010 ) and Hopea odorata Roxb ( Satiraphan et al, 2015 ). Henrischinins A-B ( 5 – 6 ) were previously isolated from Schisandra henryi ( Xue et al, 2011 ) and S. chinensis ( Song et al, 2013 ), and reported to have moderate to weak activity against HSV-2 and adenovirus ( Boemke and Tudzynski, 2009 ) and HL-60 cell lines ( Xue et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of them, metabolites 1 – 6 belong to schitriterpenoids while 7 – 9 are schinortriterpenoids. Specifically, abiesatrine J ( 3 ) was a rare C-24/C-25 double bond isomer of nigranoic acid ( 1 ) and was only found in two plants, Abies georgei Orr ( Yang et al, 2010 ) and Hopea odorata Roxb ( Satiraphan et al, 2015 ). Henrischinins A-B ( 5 – 6 ) were previously isolated from Schisandra henryi ( Xue et al, 2011 ) and S. chinensis ( Song et al, 2013 ), and reported to have moderate to weak activity against HSV-2 and adenovirus ( Boemke and Tudzynski, 2009 ) and HL-60 cell lines ( Xue et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%